DISPLACEMENT MEASUREMENT AND TRACKING USING LASER RANGE FINDER - MOHAMMED AL-AMERI, MOHAMMED AMMAR (2018)
This project aims to study and design a system of object detection, tracking and displacement measurement using Laser Range Finder (LRF). The implementation of this system is concerned within the application of security parameters and scientific researches, where the system acquires a static sensory hardware in a dynamic environment. A full utilization is carried out on the LRF sensor Hokuyo URG-04LX as an active laser scanner used to detect objects in the environment through their distance measurement from the sensor. The accomplished system is designed using two LRF sensors of Hokuyo URG-04LX facing each other for an enhanced accuracy and precision of object detection and tracking.